Pilot Study on the Effects of the Teaching Interpersonal Skills Program for Teens Program (PEHIA) - Serrano-Pintado, Isabel; Escolar-Llamazares, María-Camino; Delgado-Sánchez-Mateos, Juan (Frontiers in Psychology, 2022)
Background/Objective Social skills are essential in adolescence, both for their relational dimension and for their influence on other areas of adolescent life, so it is essential to include Social skills in the formal education of students. Method This paper presents the results of an experimental mixed factorial design pilot study in which an Interpersonal Skills Training Program for Adolescents (PEHIA1) was applied. The convenience sample consisted of 51 adolescents. An evaluation was carried out before and after the intervention, using the CEDIA (Adolescent Interpersonal Difficulties Assessment Questionnaire) and SAS-A (Social Anxiety Scale for Adolescents) questionnaires. Results The mixed factorial ANOVA show significant differences in the overall measures and in most of the subscales of both questionnaires, indicating that PEHIA is effectiveness, at least in the short term. Conclusions The results obtained in assertiveness, interpersonal relationships and public speaking suggest that the program is feasible and shows promising results in reducing anxiety. However, a larger scale study should be conducted.